Department of surgery profile - Clegg-Lamptey, J.N. (Current Challenges with their Evolving Solutions in Surgical Practice in West Africa: A Reader, 2013)
In lieu of an abstract, here is a brief excerpt of the content: •1• Department of Surgery Proﬁle Chapter 1 Department of Surgery Proﬁle J. N. Clegg-Lamptey The Department of Surgery was one of the ﬁrst Departments established in the University of Ghana Medical School. The Clinical Department currently spans the main six-storey Surgical Block, Cardiothoracic Centre, National Burns Plastic and Reconstruction centre, Accident Centre and Allied Surgery wards of the Korle Bu Teaching Hospital. It is arguably the largest department in the University of Ghana, with a teaching staff strength of 49. The Department boasts a unique blend of many generations of teachers. They include some of the pioneers who established the Department ( Professors E. A. Badoe and E.Q. Archampong) and others such as Dr. B. A. Kuma and Prof. E. D. Yeboah who have taught for many decades and trained generations of teachers and students. Their rich experience and dedication combined with the youthful dynamism and technological savvy of some of the very young teachers have greatly enriched the Department. SomepastseniormembershaveputGhanaontheworldmapthrough their innovations and achievements. They include Prof. Kwashie Quartey (who introduced the Quartey Urethroplasty operation), Prof. E. A. Badoe (Badoe intravenous ﬂuid) and Prof. Frimpong-Boateng (First black African to carry out heart transplantation). Starting off with General Surgery, the Department has expanded into nine units that are currently striving to subspecialize: 1. General Surgery, 2. Plastic Surgery, 3. Trauma and Orthopaedic Surgery, 4. Urology, 5. Neurosurgery, 6. Cardiothoracic Surgery, 7. Paediatric Surgery, 8. Ophthalmology, 9. Ear, Nose and Throat surgery. •2• Chapter 1 The ﬁrst Head of the Department was Professor Charles Easmon (in 1966) who also served as the ﬁrst Dean of the Medical School. The Department has since had many illustrious heads: Prof. C. O. Easmon 1 January 1966 – 31 December 1971 Prof. E. A. Badoe 1 January 1972 – 31March 1981 Prof. E. Q. Archampong 1 April 1981 – 31 March 1990 Prof. E. D. Yeboah 1 April 1990 – 30 September 1997 Prof. S. B. Naaeder 1 October 1997 – 31 December 2000 Prof. K. Frimpong-Boateng 1 January 2001 – 31 August 2002 Prof. R. Darko 1 September 2002 – 31 July 2008 Prof. A. A .J. Hesse 1 August 2008 – 31 July 2010 Prof. J. N. Clegg-Lamptey 1 August 2010 - Present Core Functions 1. Teaching/ Training The Department offers teaching and training of medical students in the University of Ghana Medical School during the three clinical years: First Clinical Year General Surgery, Paediatric Surgery, Urology, Neurosurgery, Orthopaedics & Trauma: Second Clinical Year ENT, Ophthalmology. Third Clinical Year General Surgery, Paediatric Surgery, Cardiothoracic Surgery, Plastic Surgery, Orthopaedic Surgery, Neurosurgery, Urology. We also offer training to students from other Schools and Postgraduate colleges: • Dental students from the University of Ghana Dental School; • Nursing students from School of Nursing; •3• Department of Surgery Proﬁle • Postgraduate surgical trainees of the Ghana College of Physicians and Surgeons and the West African College of Surgeons; • Foreign medical students on Exchange and Elective programmes; • Foreign-trained doctors, in preparation for Ghana Medical & Dental Council examinations; • House ofﬁcers and nursing interns. 2. Service The Department provides specialist consultancy and theatre services for referred surgical cases from all over the country and the West African subregion. Many senior members go on outreach programmes to various parts of the country, and some offer weekly breast screening to the public in the Korle Bu Teaching hospital. 3. Research The Department undertakes research in all its specialties and also does collaborative research with other institutions such as the University of Ghana, Ministry of Health, and external agencies. There is an active monthly Research Forum that promotes research in the department. Future Directions Teaching sites With the forthcoming relocation of the College of Health Sciences to Legon campus, the Department envisages that it will soon be operating from two main sites (Legon and Korle Bu) as well as the Military Hospital. We will explore the possibility of additional sites so that medical students can be taught more effectively in the light of increasing student numbers. Manpower development More strenuous efforts at recruiting young faculty will continue. The Department hopes to have young faculty in every unit who are motivated to develop their specialties. •4• Chapter 1 Young faculty will be trained in Israel under the programme to build a new Teaching Hospital at the Legon campus. We will also look for other avenues for young specialists to spend some time in highly specialized centres overseas in order to encourage sub-specialization. Academic degrees Senior members will actively encourage young specialists to aim at academic degrees...